2019
DOI: 10.1007/s10763-019-09964-5
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Field Mathematics Teachers’ Beliefs and Practices: an Examination of Change and Tensions Using Zone Theory

Abstract: This paper describes an empirical study examining action research papers submitted by a group (n=81) of out-of-field mathematics teachers as part of a professional development programme in Ireland. Utilising document analysis, the papers were qualitatively analysed for evidence of teachers' beliefs and practices with respect to the teaching and learning of mathematics. In particular, demonstration of directtransmission and constructivist beliefs and practices was explored. The authors draw on Valsiner's zone t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…First, to partially counter the possibility that teachers may have overreported the effects of participation in the programme, we followed Desimone's (2009) recommendation to interpret teachers' self-reports of behavioural change in the context of the epistemological and pedagogical beliefs elicited via other survey items. Second, our claims are supported by previous studies, conducted by Lane andFaulkner (2021), that involved different cohorts of PDMT participants and different data sources and analysis methods. Both of these studies collected data on self-reported beliefs and classroom practices before and after teachers experienced specific components of the PDMT programme (action research for the former study; pedagogy workshops for the latter study); and both studies found evidence of a reported shift away from a traditional, teacher-led style to more student-centred, inquiry-based pedagogies that emphasise development of mathematical understanding.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…First, to partially counter the possibility that teachers may have overreported the effects of participation in the programme, we followed Desimone's (2009) recommendation to interpret teachers' self-reports of behavioural change in the context of the epistemological and pedagogical beliefs elicited via other survey items. Second, our claims are supported by previous studies, conducted by Lane andFaulkner (2021), that involved different cohorts of PDMT participants and different data sources and analysis methods. Both of these studies collected data on self-reported beliefs and classroom practices before and after teachers experienced specific components of the PDMT programme (action research for the former study; pedagogy workshops for the latter study); and both studies found evidence of a reported shift away from a traditional, teacher-led style to more student-centred, inquiry-based pedagogies that emphasise development of mathematical understanding.…”
Section: Discussionsupporting
confidence: 67%
“…Desimone (2009) notes that it is rare for a single study to investigate all four elements of this model; in particular, there are significant methodological difficulties in designing evaluations that measure the specific effects of professional development on student achievement. Our own research has concentrated on analysing the critical features of the PDMT programme (Step 1 in Desimone's model; see Goos et al 2020) and its effect on the teachers who participated in the programme (Steps 2 and 3; see Lane and Ní Ríordáin 2020;Ní Ríordáin, Paolucci, and O'Dwyer 2017;O'Meara and Faulkner 2021). In this paper, we further examine the impact of the PDMT on teachers' beliefs and pedagogical approaches as key elements in Desimone's (2009) model of teacher change.…”
mentioning
confidence: 99%
“…Hence, pre-service teachers may have had more positive beliefs in terms of mathematics teaching self-efficacy beliefs. Studies also enlightened those pre-service and in-service teachers' understanding and beliefs regarding training may be changed, their self-efficacy towards mathematics increases, they are more motivated to use innovative approaches for mathematics lessons and their anxiety about teaching mathematics decreases when effectively designed educational content is provided (Ginsburg & Uscianowski, 2017;Jao, 2018;Jett, 2018;Lane & Ríordáin, 2020;Rogers et al, 2015). From this point of view, these kinds of training may be suggested for teacher education to integrate mathematics and children's literature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of upmost importance to understand the pre-service and in-service teachers' beliefs as intentions' function to ensure their professional development (Qhobela & Moru, 2014). It is also known that teachers' beliefs about teaching might be changed through professionally designed training (Lane & Ríordáin, 2020). Besides, pre-service and in-service teachers encounter similar difficulties in terms of barriers to this integration Can et al, 2020;Prendergast et al, 2019), and the development of practitioner competencies regarding integration has become increasingly popular in recent years (Edelman et al, 2019).…”
Section: Aim and Significance Of The Studymentioning
confidence: 99%
“…Explicating the characteristics and impacts of study groups as an approach to teacher learning will be helpful to mathematics educators, researchers, and policymakers as they design PD activities and/or conduct research (Borko & Potari, 2020;Darling-Hammond et al, 2017). More importantly, teaching 'outof-field' is a present obstacle in mathematics education in many countries, and the development of PD programs aimed at upskilling non-specialist teachers is a growing field (see Lane & Ní Ríordáin, 2020). The findings presented in this study contribute to our understanding of supporting non-specialist mathematics teachers' knowledge needed to teach the subject and plausibly improving teacher and teaching quality (du Plessis, 2015;Faulkner et al, 2019).…”
Section: Significance Of the Studymentioning
confidence: 99%